Household Production, Services and Monetary Policy - Lonkeng Ngouana, Constant (IMF Working Papers; Working Paper ;, 2012)
A distinctive feature of market-provided services is that some of them have close substitutes at home. Households may therefore switch between consuming home and market services in response to changes in the real wage - the opportunity cost of working at home - and changes in the price of market services. In order to analyze and quantify the implications of this trade-off for monetary policy, I embed a household sector into an otherwise standard sticky price DSGE model, which I calibrate to the U.S. economy. The results of the model are twofold. At the sectoral level, household production augments the service sector's New Keynesian Phillips curve with a sizable extra component that co-moves negatively with the output gap term, lowering the incentive of service sector firms to change their prices. This mechanism endogenously amplifies the real effects of a monetary shock in that sector, unlike in the nondurable goods sector for which households cannot manufacture substitutes at home. At the aggregate level, household production also implies more sluggish prices and a stronger response of real macroeconomic variables to a monetary shock. Some empirical support for this theory is provided.